Antibiotic resistance in major rivers in the world: A systematic review on occurrence, emergence, and management strategies - Singh R.; Singh A.P.; Kumar S.; Giri B.S.; Kim K.-H. (My University, 2025)
The occurrence of antibiotics and antibiotic resistance genes in riverine systems has become a growing concern worldwide. Risk prediction of antibiotic resistance is difficult as the continuous addition of new antibiotics complicate the antibiotic resistome. As rivers flow with heavy antibiotic burdens, antibiotic resistance develops rapidly and disseminates into various environmental compartments. The analysis of antibiotic contamination-driven resistance in global rivers provides a clear picture of the consequences in the near future. In this review, an extensive literature survey along with the analysis on the relevant data was carried out to offer a better knowledge on the global trend of antibiotic resistance. Although the most common resistance was reported against tetracycline and sulfonamide class of antibiotics, the trend of resistance against advanced generation antibiotics such as β-lactam is alarming. Furthermore, non-therapeutic use of antibiotics as growth promoters has become more frequent than clinical use as a major driver of resistance dissemination. Mechanistically, integrons and mobile genetic elements are suggested as one of the important media for resistance gene transfer. Considering the significance of this emerging issue, special emphasis is placed on the sources, fate, and possible management strategies to mitigate the threat of antibiotic resistance. This review covers the environmental footprints of the antibiotic contamination-mediated emergence and dissemination of antibiotic resistant bacteria and genes in global rivers. As such, the distribution pattern of antibiotic contamination and resistance determinants in various rivers worldwide has been described with a note of its long term impact. The information presented in this review may be useful to policy makers, clinicians, and pharmaceutical companies to tackle the epidemiology of antibiotic resistance as a global threat. © 2019 Elsevier Ltd